Bipolar disorder - Goodwin, G (2012)
Bipolar disorder (BD) is the episodic disturbance of mood into depression or elation. Bipolar I disorder (BD-I) is defined by mania; bipolar II disorder (BD-II) by major depression and hypomania. BD is heritable; many gene variants of small effect contribute to risk. Anxiety co-morbidity is very common. The management of bipolar disorder usually requires long-term treatment. Because BD combines chronicity with considerable patient autonomy, psycho-education is key to management. Severe manic or mixed episodes should be treated by oral administration of an antipsychotic or valproate. The treatment of bipolar depression is currently controversial. For an early treatment effect quetiapine is useful. Lamotrigine requires dose titration but is well tolerated and a possible monotherapy in BD-II. Antidepressant use is not recommended as monotherapy for bipolar patients but should be given with long-term treatments likely to protect the patient from manic relapse. Relative or even marked treatment resistance may occur in depressed bipolar patients. The available medicines for long-term treatment are often more effective against one illness pole than the other, so are often used in combinations dictated by the burden of illness. If this is predominantly mania, one combines the most anti-manic agents (e.g. lithium, valproate, an antipsychotic); where depressive, lamotrigine or quetiapine may be more appropriate. © 2012 Elsevier Ltd. All rights reserved.